Comparison of Lidocaine and Prilocaine for Intravenous Regional Anesthesia of the Whole Lower Extremity. Issue 3 (July 1987) - Valli, Harri K.; Rosenberg, Per H.; Hekali, Riitta
Abstract : The quality as well as safety of intravenous regional anesthesia (IVRA) of the leg achieved with 6 mg/kg of 0.4% prilocaine (13 patients) and with 6 mg/kg of 0.4% lidocaine (13 patients) were compared. There was no difference between the two groups in the development of sensory or motor blockade. Four patients, two in each group, had pain from surgery, whereas 14 patients (9 prilocaine, 5 lidocaine) (mean tourniquet time: 81 minutes) needed intravenous analgesics and sedatives because of tourniquet-induced pain; the cuff had to be deflated before the end of surgery in three patients. One patient in the prilocaine group (plasma concentration at 2 minutes of 0.74 μg/ml) and six patients in the lidocaine group (plasma concentration at 2 minutes of 1.04-5.49 μg/ml) showed signs of mild central nervous system toxicity. More severe symptoms were experienced by one patient in the prilocaine group (5.33 μg/ml) and three patients in the lidocaine group (2.99-7.79 μg/ml). Methemoglobin levels rose moderately (10-fold) in the patients given prilocaine. Toxicologic considerations warrant close observation of the patients and seem to favor the use of prilocaine instead of lidocaine for IVRA of the leg. Furthermore, tourniquet-induced pain becomes a major problem when the tourniquet time is long.